COVID-19 cross-sectional study in Maricá, Brazil: The impact of vaccination coverage on viral incidence - Frauches, Thiago Silva; Costa, Carlos Alberto de Senna; Rodrigues, Claudia dos Santos; de Azevedo, Marcelo Costa Velho Mendes; Ferreira, Michelle de Moraes; Ramos, Hanna Beatriz Vieira da Silva; de Souza Junior, Wilson Rodrigues; Costa, Andréa Ribeiro; Camargo, Adriana Cardoso; Alonso, Adriana Halfeld; dos Santos, Fábio Álvaro; Oliveira, Hércules da Silva; et al. (PloS one, 2022)
Population surveillance in COVID-19 Pandemic is crucial to follow up the pace of disease and its related immunological status. Here we present a cross-sectional study done in Maricá, a seaside town close to the city of Rio de Janeiro, Brazil. Three rounds of study sampling, enrolling a total of 1134 subjects, were performed during May to August 2021. Here we show that the number of individuals carrying detectable IgG antibodies and the neutralizing antibody (NAb) levels were greater in vaccinated groups compared to unvaccinated ones, highlighting the importance of vaccination to attain noticeable levels of populational immunity against SARS-CoV-2. Moreover, we found a decreased incidence of COVID-19 throughout the study, clearly correlated with the level of vaccinated individuals as well as the proportion of individuals with detectable levels of IgG anti-SARS-CoV-2 and NAb. The observed drop occurred even during the introduction of the Delta variant in Maricá, what suggests that the vaccination slowed down the widespread transmission of this variant. Overall, our data clearly support the use of vaccines to drop the incidence associated to SARS-CoV-2.